A FLIPR Assay for Discovery of GABAA Receptor Modulators of Natural Origin - Faleschini, Maria Teresa; Maier, Anne; Fankhauser, Sarah; Thasis, Katharina; Hebeisen, Simon; Hamburger, Matthias; Butterweck, Veronika (Planta Medica, 2019)
A fluorometric imaging plate reader (FLIPR) assay utilizing Chinese hamster ovary (CHO) cells stably transfected with GABAA receptors of α1β2γ2 subunit composition was evaluated and validated for rapid screening of plant extract libraries and efficient localization of active compounds in extracts. Validation was performed with pure compounds and extracts known to contain allosteric GABAA receptor modulators. Plants extracts that had been previously reported as active in an assay using Xenopus laevis oocytes transiently expressing GABAA receptors of α1β2γ2 subunit composition were also active in the FLIPR assay. A protocol for HPLC-based activity profiling was developed, whereby separations of 0.4 – 1.2 mg of extracts on an analytical HPLC column were found to be sufficient for the sensitivity of the bioassay. The protocol successfully localized the activity of known GABAergic natural products, such as magnolol in Magnolia officinalis, valerenic acid in Valeriana officinalis, and piperine in Piper nigrum extract. EC50 values of compounds (magnolol: 4.81 ± 1.0 µM, valerenic acid: 12.56 ± 1.2 µM, and piperine: 5.76 ± 0.7 µM) were found to be comparable or lower than those reported using Xenopus oocyte assays.
Keywords: FLIPR; magnolol; valerenic acid; piperine; diazepam; GABAA